2004
DOI: 10.1007/s10350-003-0052-3
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Study of Lateral Pelvic Lymph Nodes: Implications in the Treatment of Rectal Cancer

Abstract: The mean number of lymph nodes found in lateral pelvic wall compartments was 28.6 per specimen. The group containing most lymph nodes lies in the obturator fossa. Complete excision of hypogastric lymph nodes demands a deep pelvic dissection of neurovascular structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 57 publications
4
13
0
1
Order By: Relevance
“…They classified the nodes into three regions: presacral, hypogastric, and obturator group. This study showed that the highest incidence of nodal involvement was found along the internal pudendal artery region, the internal iliac artery region and the obturator region, considering these regions combined as a "vulnerable field" (11). The lymph nodes from the internal iliac artery were found predominantly above the pelvic nerve plexus but reaching the deep pelvic veins, hence, demanding a deep pelvic dissection of the neurovascular structures (11).…”
Section: Importance Of Lateral Lymph Node Metastasismentioning
confidence: 93%
See 1 more Smart Citation
“…They classified the nodes into three regions: presacral, hypogastric, and obturator group. This study showed that the highest incidence of nodal involvement was found along the internal pudendal artery region, the internal iliac artery region and the obturator region, considering these regions combined as a "vulnerable field" (11). The lymph nodes from the internal iliac artery were found predominantly above the pelvic nerve plexus but reaching the deep pelvic veins, hence, demanding a deep pelvic dissection of the neurovascular structures (11).…”
Section: Importance Of Lateral Lymph Node Metastasismentioning
confidence: 93%
“…It is believed that disease in this area is because of the lymphatic drainage from the lower rectum exceeds the mesorectum through the lateral ligament and then along the internal iliac artery and consequently into the obturator space. This theory explains why the obturator region has the highest rate of nodal involvement and it should be examined as a significant area of cancer spread in these tumors (11).…”
Section: Importance Of Lateral Lymph Node Metastasismentioning
confidence: 99%
“…There was only one report from Canessa et al [21] describing size of lateral pelvic lymph nodes in diseasefree cadavers. However, they did not evaluate tumorbearing lateral pelvic lymph nodes.…”
Section: Discussionmentioning
confidence: 96%
“…The next most frequent site of lateral pelvic lymph node metastasis was the obturator area. Canessa et al 17 reported an anatomic study using cadaveric dissection, in which most of the metastatic lymph nodes found in the lateral pelvic area were located in the obturator area. Therefore, we believe that the next AJCC cancer staging manual should mention not the external iliac area but the obturator area as a site of regional lymph node metastasis in lower rectal cancer.…”
Section: Discussionmentioning
confidence: 99%